The relationship between quality of caregiver-child interaction, parenting disciplinary practices and children's social behavioural problems - Syarifah Maisarah binti Syed Alwi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The present study was carried out to understand the relationship between quality of caregiver-child interaction, parenting disciplinary practices, and social behavioural problems among children who attend child care centres. It aims to examine (i) the relationship between the quality of caregiver-child interaction in child care centres and children's social behavioural problems, (ii) the relationship between parenting disciplinary practices and children's social behavioural problems, and (iii) the interaction effect of parenting disciplinary practices on the relationship between the quality of caregiver-child interaction in child care centres and social behavioural problems of children. To achieve these goals, data were collected from 112 children between 4-6 years of age who attend child care centres around Kuala Lumpur and Selangor. The results show that (i) children were rated low in the Strength and Difficulty Questionnaire (SDQ) when their caregiver provides high quality caregiver-child interaction, (ii) low scores on the Parenting Scale (PS) were associated with low scores on the SDQ, and (iii) parenting disciplinary practices did not moderate the effect of the quality of caregiver-child interaction on children's social behavioural problems. These findings are discussed with respect to the current literature on caregiver-child interaction and parenting disciplinary practices.